DEVELOPMENT OF APPLICATION-BASED WORD WALL GAME MEDIA ON NATURAL SCIENCE SUBJECTS FOR ELEMENTARY SCHOOL STUDENTS - Fikri Abdillah; Moh. Balya Ali Syaban (Universitas Majalengka, 2023)
In the industrial era 4.0 at this time, the use of technology in the education aspect, by being applied to learning media, tends to be less than optimal where there are still teachers who do not use learning media by utilizing technology in the teaching and learning process. Teachers only use conventional learning media by using textbooks as learning media, so learning tends to be boring and less optimal. This study aims to develop Word Wall learning media and to determine the feasibility of Word Wall media in improving learning outcomes of Natural Sciences in grade V Elementary School. This study uses Research and Development (R&D) research methods, with the ADDIE model using five steps 1. Analysis 2. Design 3. Development 4. Implementation 5. Evaluate. This research was conducted at SDN Kemayoran 07 Pagi, Central Jakarta. They collected the information and data needed by distributing questionnaires to media experts in the form of 20 questions, material experts in the form of 17 questions and education experts in the form of 15 questions. The validation results from the experts in this study found that media expert validation was categorized as “very feasible”, material expert validation was “very feasible”, and educational expert validation was categorized as “very feasible”. Furthermore, small and large group trials were categorized as “very feasible”. So it can be concluded in this study that Word Wall learning media is very feasible in improving student learning outcomes in the subject of science Natural knowledge grade V elementary school. Di era industri 4.0 pada saat ini pemanfaatan teknologi pada aspek Pendidikan, dengan diaplikasikan pada media pembelajaran cenderung masih kurang maksimal dimana guru masih ada yang tidak mengunakan media pembelajaran dengan memanfaatkan teknologi pada proses belajar mengajar. Guru hanya mengunakan media pembelajaran yang konvensional dengan mengunakan buku pelajaran sebagai media pembelajaran sehingga pembelajaran cenderung membosankan dan kurang makimal. Penelitian ini bertujuan untuk mengembangkan media pembelajaran Word Wall serta untuk mengetahui kelayakan dari media Word Wall dalam meningkatkan hasil belajar Ilmu Pengetahuan Alam kelas V Sekolah Dasar. Penelitian ini mengunakan metode penelitian Research and Development (R&D), dengan model ADDIE mengunakan lima Langkah 1. Analysis 2. Design 3. Development 4. Implementation 5. Evaluate. Penelitian ini dilakukan di SDN Kemayoran 07 Pagi Jakarta Pusat. Pengumpulan informasi dan data yang dibutuhkan dengan menyebarkan angket kepada ahli media berupa 20 soal, ahli materi berupa 17 soal dan ahli Pendidikan berupa 15 soal. Hasil validasi dari para ahlli pada penelitian ini mendapatkan, validasi ahli media dikategorikan “sangat layak”, validasi ahli materi “sangat layak” serta validasi ahli Pendidikan dikategorikan “sangat layak”. Selanjutnya dilakukan uji coba kelompok kecil dan kelompok besar dengan dikategorikan “sangat layak”. Maka dapat disimpulkan dalam penelitian ini media pembelajaran Word Wall sangat layak dalam meningkatkan hasil belajar siswa pada mata pekajaran Ilmu Pengetahuan Alam kelas V sekolah dasar.